Trade, foreign exchange, and energy policies in the Islamic Republic of Iran : reform agenda, economic implications, and impact on the poor - Jensen, Jesper Bo (Policy research working paper, 2002)
Reflecting the large initial distortions, trade, exchange rate, and energy reforms could generate large welfare gains for the Islamic Republic of Iran. If combined with direct income payments to all households (not just the poor), the poor would benefit enormously. The authors show that well intentioned policies of commodity subsidies for the poor can have perverse effects